PENGARUH BEBAN KERJA, KEPUASAN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PT GUNAWAN DIANJAYA STEEL TBK - Fahril Oktavio; Mei Indrawati (Jurnal Ekonomi, Bisnis dan Social, 2023)
This study aims to analyze and prove the effect of workload, job satisfaction and work environment on employee performance. The population in this study amounted to 53 respondents. This type of research uses explanatory research. The data collection method used in this study is a quantitative method using independent and dependent variables. The data analysis method used in this study is the classical assumption test, descriptive statistical analysis, descriptive analysis, multiple linear regression analysis, coefficient of determination and hypothesis testing. Data analysis was performed using statistics with SPSS and excel tools. Based on the results of data analysis using the t test it is known that workload has a significant effect on employee performance, job satisfaction has a significant effect on employee performance, the work environment has a significant effect on employee performance, while based on data analysis using the F test it is known that workload, job satisfaction, and work environment simultaneously have a significant effect on the performance of employees of PT Gunawan Dianjaya Steel Tbk.